Magnaporthe oryzae endoplasmic reticulum membrane complex regulates the biogenesis of membrane proteins for pathogenicity - Liu, Ning (The New phytologist, 2023)
© 2023 The Authors New Phytologist © 2023 New Phytologist Foundation.